Anxiety, sleep disorders and self‐efficacy among nurses during COVID‐19 pandemic: A large cross‐sectional study - Simonetti, Valentina; Durante, Angela; Ambrosca, Rossella; Arcadi, Paola; Graziano, Giusi; Pucciarelli, Gianluca; Simeone, Silvio; Vellone, Ercole; Alvaro, Rosaria; Cicolini, Giancarlo (Journal of clinical nursing, 2021)
Aim and objectives To assess the prevalence of anxiety, sleep disorders and self‐efficacy and their predicting factors among nurses facing COVID‐19. Background The spread of COVID‐19 throughout the world determined a series of modifications of several National Health Service organisations, with a potential series of psychological consequences among nurses, who were particularly afflicted by this situation of changes and precariousness. Design A cross‐sectional study was carried out from February–April 2020. Methods A total of 1,005 nurses employed in different Italian hospital wards, during the COVID‐19 pandemic, were recruited. Analyses were based on descriptive statistics and multivariate logistic regression. The STROBE checklist for cross‐sectional studies was used in this study. Results The prevalence of sleep disturbances, moderate anxiety and low self‐efficacy was 71.4%, 33.23% and 50.65%, respectively. We found a positive correlation between anxiety and sleep quality (0.408; p < .0001) and negative correlations between self‐efficacy and anxiety (−0.217; p < .0001) and sleep quality and self‐efficacy (−0.134; p < .0001). The factor independently associated with all variables was gender. Females were more prone to sleep disturbances, anxiety and low levels of self‐efficacy than males (p < .05). Conclusions The prevalence of anxiety, sleep disorders and low self‐efficacy among Italian nurses during the COVID‐19 pandemic was high. Healthcare managers should recognise and consider these results to reduce the risk of the onset of major mental problems that could result in post‐traumatic stress disorder. Relevance to clinical practice Nurses facing major incidents as COVID‐19 pandemic are among healthcare personnel exposed to a high risk to develop psychological disturbance that should be assessed and recognised, in order to find helpful coping strategies to inform support services and avoid to hesitate in post‐traumatic stress disorders.